CAN WE PREDICT TREND IN TECHNOLOGY? - Lovrekovic, Zoran (Journal of process management and new technologies, 2021)
This paper shows that the foundations of today 's information technology were laid mainly in the 1960s and 1970s. Even the World Wide Web was founded in the 1990s. Following the philosophy of Moore's Law, and generalizing the findings from the past, it is possible to conclude that, in the same way, the foundations of the technology that will mark the next two decades have already been laid these days. Based on that, predictions that will be technological trends in the next 20 years can be confirmed with great certainty. Further development and ubiquitous application of artificial intelligence, IoT, and 5G networking will certainly fundamentally change our lives.
Keywords: Technological predictions; computer networks; Moore's law; artificial intelligence; Augmented reality; spatial web